Evolution of microstructure under different homogenization conditions and its effect on recrystallization processes during hot rolling of AA5182 alloy - Ćitić, Aleksandar; Radetić, Tamara; Rajković, Filip; Prelević, Dejan; Popović, Miljana (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
<!– [if gte mso 9]> 15.00 <![endif]–><!– [if gte mso 9]> Normal 0 false false false EN-US JA X-NONE <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–><span style="font-size: 12.0pt; font-family: ’Times New Roman’,serif; mso-fareast-font-family: ’MS Mincho’; mso-fareast-theme-font: minor-fareast; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This study investigates microstructure development of AA5182 Al-Mg alloy under various homogenization conditions and how these conditions affect recrystallization processes and texture development during the laboratory hot-rolling. Homogenization treatments were conducted for 16 h at 490°C and at 550°C for various times. Scanning electron microscopy (SEM) characterization including energy-dispersive X-ray spectroscopy (EDX) revealed the presence of Al3(Fe,Mn) and Alm(Fe,Mn) phases as Fe/Mn-bearing microconstituents in as-cast state. These transformed into Al6(Fe,Mn) and α-Al(Fe,Mn)Si during homogenization treatments. The treatments also led to precipitation of Al6(Mn,Fe) and α-Al(Fe,Mn)Si dispersoid particles. Results of electron backscattered diffraction (EBSD) indicated that a weak deformation texture was present after the hot-rolling. The morphology of grains and degree of restoration were significantly influenced by homogenization conditions. The distribution and density of dispersoids had a strong effect on the mechanisms of recovery and recrystallization.